Cycle‐based variable speed limit methodology for improved freeway merging. Issue 10 (25th July 2017) - Zhang, Li; Zhang, Lei; Hale, David K.; Hu, Jia; Huang, Zhitong
Abstract : Studies and field implementations demonstrate that variable speed limit (VSL) systems help freeway traffic congestion mitigations. This study presents a cycle‐based variable speed limit (CVSL) strategy that could variate speed limits in the upstream segment of freeway merging areas. CVSL reduces speed limits in a fraction of a cycle. This variation creates artificial gaps on freeway mainlines, which in turn increases merging opportunities for incoming on‐ramp vehicles. CVSL retains VSL's benefit in reducing delays while overcoming its shortcoming of no significant throughput increase. The authors establish analytical CVSL delay models, including freeway mainline and ramp delays with CVSL speed as a decision variable, and propose a robotic solution method to minimise the delays. The delay model and solutions are implemented and independently evaluated in microscopic traffic simulation. Particularly, the CVSL system is implemented and interfaced with the transportation flow open‐source microscopic model (ETFOMM). Detector information from ETFOMM is fed into the delay model, and the optimised speed limit is fed back to ETFOMM. Two performance measures, total travel delay and throughput, are used to evaluate the CVSL system. Their simulation evaluation indicated up to 16% delay reduction and 6% throughput increase. This CVSL strategy is ready for field evaluation.